Pathological α-synuclein distribution in subjects with coincident Alzheimer’s and Lewy body pathology - Toledo, Jon B.; Gopal, Pallavi; Raible, Kevin; Irwin, David J.; Brettschneider, Johannes; Sedor, Samantha; Waits, Kayla; Boluda, Susana; Grossman, Murray; Van Deerlin, Vivianna M.; Lee, Edward B.; Arnold, Steven E.; et al. (Acta neuropathologica, 2016)
We investigated the distribution patterns of Lewy body-related pathology (LRP) and the effect of coincident Alzheimer disease (AD) pathology using a data-driven clustering approach that identified groups with different LRP pathology distributions without any diagnostic or researcher’s input in two cohorts including: Parkinson disease patients without (PD, n = 141) and with AD (PD-AD, n = 80), dementia with Lewy bodies subjects without AD (DLB, n = 13) and demented subjects with AD and LRP pathology (Dem-AD-LB, n = 308). The Dem-AD-LB group presented two LRP patterns, olfactory-amygdala and limbic LRP with negligible brainstem pathology, that were absent in the PD groups, which are not currently included in the DLB staging system and lacked extracranial LRP as opposed to the PD group. The Dem-AD-LB individuals showed relative preservation of substantia nigra cells and dopamine active transporter in putamen. PD cases with AD pathology showed increased LRP. The cluster with occipital LRP was associated with non-AD type dementia clinical diagnosis in the Dem-AD-LB group and a faster progression to dementia in the PD groups. We found that (1) LRP pathology in Dem-AD-LB shows a distribution that differs from PD, without significant brainstem or extracranial LRP in initial phases; (2) coincident AD pathology is associated with increased LRP in PD indicating an interaction; (3) LRP and coincident AD pathology independently predict progression to dementia in PD, and (4) evaluation of LRP needs to acknowledge different LRP spreading patterns and evaluate substantia nigra integrity in the neuropathological assessment and consider the implications of neuropathological heterogeneity for clinical and biomarker characterization.